Microbial profile with their antimicrobial susceptibility pattern in ear discharge of Chronic suppurative otitis media patients at a tertiary care hospital in Durgapur - Robert Priscilla,; Aditya Tiwari,; Jiwesh Kumar Thakur,; Pinki Kumari, (Asian Journal of Medical Sciences, 2022)
Background: Chronic suppurative otitis media (CSOM) is a persistent middle ear disease with high risk of irreversible complications in absence of timely management. It is a massive health problem in India having the highest prevalence rate (>4%) requiring urgent attention. Aims and Objectives: The aim of the study was to find out risk factors, microbiological profile, with their susceptibility pattern, and of ear discharge in CSOM patients to provide guidelines for the empirical treatment. Materials and Methods: Ear discharge samples from 135 clinically diagnosed CSOM patients were collected and processed. Microbial isolates were identified and drug susceptibility testing was conducted using Kirby-Bauer disc diffusion method. Results: Pseudomonas species (59/135, 43.70%) was the predominant isolate followed by Staphylococcus species (37/135, 27.40%) while Aspergillus species (10/12, 83.33%) was the predominant fungus isolated. No anaerobic bacteria were isolated on culture. Gram-negative bacilli were most susceptible to Meropenem (100%) and Amikacin (100%) while Pseudomonas species was to Imipenem (98.35%). Gram-positive cocci showed 100% susceptibility to Vancomycin, Linezolid, and Doxycycline. Conclusion: A continuous and periodic evaluation of microbiological pattern of CSOM and antimicrobial sensitivity of isolates is necessary for forming the basis of empirical treatment which shall aid in decreasing the potential risk of complications. Further, accurate and timely identification, knowledge of the pathogens, and judicious use of antibiotics are the need of the hour.